Stability and attractivity of solutions of differential equations with impulses at fixed times. (2000) - Sivasundaram, S.; Vassilyev, S.
Abstract : In this paper we consider the dynamics of solutions of impulsive differential equations with fixed time moments of impulsive effects on the basis of comparison methods and vector Lyapunov functions. We propose sufficient conditions on the following dynamic properties: stability, attractivity, and some combinations of them.